2021
DOI: 10.3390/polym13101664
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Antimicrobial Neem Leaves Extract Based Macroalgae Biofilms for Potential Use as Active Dry Packaging Applications

Abstract: Antimicrobial irradiated seaweed–neem biocomposite films were synthesized in this study. The storage functional properties of the films were investigated. Characterization of the prepared films was conducted using SEM, FT-IR, contact angle, and antimicrobial test. The macroscopic and microscopic including the analysis of the functional group and the gas chromatography-mass spectrometry test revealed the main active constituents present in the neem extract, which was used an essential component of the fabricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The 1087.21 cm -1 wave length (Figure 4) have a C-O-C stretch (dialkyl), C-O stretch a vibration type and assigned functional group was ether and alcohol. The C-H stretching vibration modes in the hydrocarbon chains were found at 2900 cm -1 peak values (Oyekanmi et al, 2021). The peak values pointed out the occurrence of OH connecting vibrations from minor phenols, alcohol primer, alkene, C=C aromatic, carboxylic acid groups and phenolic groups that assigned (Vijayarathna and Sasidharan, 2012).Whereas, the peaks values at 1734 cm -1 matching to the stretching vibrations of the C=O in carboxylic acids, aldehydes and ketones (Oyekanmi et al, 2021).…”
Section: Fig 9 Neem Leaves Microwave Extract Ftir Spectramentioning
confidence: 95%
See 3 more Smart Citations
“…The 1087.21 cm -1 wave length (Figure 4) have a C-O-C stretch (dialkyl), C-O stretch a vibration type and assigned functional group was ether and alcohol. The C-H stretching vibration modes in the hydrocarbon chains were found at 2900 cm -1 peak values (Oyekanmi et al, 2021). The peak values pointed out the occurrence of OH connecting vibrations from minor phenols, alcohol primer, alkene, C=C aromatic, carboxylic acid groups and phenolic groups that assigned (Vijayarathna and Sasidharan, 2012).Whereas, the peaks values at 1734 cm -1 matching to the stretching vibrations of the C=O in carboxylic acids, aldehydes and ketones (Oyekanmi et al, 2021).…”
Section: Fig 9 Neem Leaves Microwave Extract Ftir Spectramentioning
confidence: 95%
“…The C-H stretching vibration modes in the hydrocarbon chains were found at 2900 cm -1 peak values (Oyekanmi et al, 2021). The peak values pointed out the occurrence of OH connecting vibrations from minor phenols, alcohol primer, alkene, C=C aromatic, carboxylic acid groups and phenolic groups that assigned (Vijayarathna and Sasidharan, 2012).Whereas, the peaks values at 1734 cm -1 matching to the stretching vibrations of the C=O in carboxylic acids, aldehydes and ketones (Oyekanmi et al, 2021). Carboxylic acid esters reported maximum antifungal activities against Aspergillus niger, Candida albicans and Cryptococcus neoformans.…”
Section: Fig 9 Neem Leaves Microwave Extract Ftir Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…In the last couple of years, several groups have shown that food preservation films that are made from polyethylene or sustainable materials such as seaweed can be manufactured to incorporate neem leaf extracts, neem oil, and other plant-based products (e.g., turmeric and curcumin) ( Ahmed et al, 2022 ). The resulting composite films are shelf-stable, block ultraviolet light, and have increased antifungal and antibacterial activities against C. albicans and a wide range of Gram-negative and Gram-positive organisms, including E. coli , S. aureus , Pseudomonas aeruginosa , and Bacillus subtilis ( Sunthar et al, 2020 ; Uthaya Kumar et al, 2020 ; Oyekanmi et al, 2021 ; Subbuvel and Kavan, 2021 ). Furthermore, the ability of A. indica to prevent activity of food-spoiling fungi is evident by several recent reports that outline the following: 1) the ability of neem oil to prevent the growth of the grape product-spoiling species Aspergillus carbonarius and to inhibit the production of mycotoxin by strains of this fungus ( Rodrigues et al, 2019 ), 2) the ability of neem leaves to prevent the production of aflatoxins by Aspergillus parasiticus during long-term storage of rice, wheat, and maize ( Sultana et al, 2015 ), 3) the ability of neem seed methanol and ethanol extracts to inhibit Aspergillus flavus and A. parasiticus by 10% in the context of maize storage ( An et al, 2019 ), 4) the ability of multiple neem seed, bark, and leaf extracts to inhibit the growth of three major potato-spoiling fungi, Aspergillus niger , Fusarium oxyporium , and Pythium spp., by 72–100% ( Ezeonu et al, 2019 ), and 5) the ability of aqueous neem leaf extract to inhibit growth of A. niger and A. parasiticus , as well as to detoxify aflatoxin B1 and ochratoxin A in vivo ( Hamad et al, 2021 ).…”
Section: Antibacterial Evidencementioning
confidence: 99%